2021
DOI: 10.1177/09544062211042051
|View full text |Cite
|
Sign up to set email alerts
|

Increase of energy efficiency ratio of a direct evaporative cooler by dynamic behavior with energy and exergy analysis

Abstract: The present research is about increasing the energy efficiency ratio (EER) in current direct evaporative coolers (DEC) in Iran. Increasing the cooling load and reducing the electrical energy consumption simultaneously (increasing the energy efficiency ratio (EER)) in DEC are the main goals of manufacturers and consumers of this device. When the circulation water pump runs continuously (static state), the circulation water rate is about 1.89 to 2.90 times of the amounts recommended in the reasonable standards. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…9 Omidi et al used energy analysis and exergy analysis to improve the energy efficiency ratio of direct evaporative cooling systems. 10 Santos et al used numerical simulation to study the changes in energy and exergy during the evaporative cooling process of the air washer. They found that the inlet air's optimal temperature and humidity parameters do not match the optimal thermodynamic performance of the equipment.…”
Section: Research Statusmentioning
confidence: 99%
“…9 Omidi et al used energy analysis and exergy analysis to improve the energy efficiency ratio of direct evaporative cooling systems. 10 Santos et al used numerical simulation to study the changes in energy and exergy during the evaporative cooling process of the air washer. They found that the inlet air's optimal temperature and humidity parameters do not match the optimal thermodynamic performance of the equipment.…”
Section: Research Statusmentioning
confidence: 99%
“…Several investigations have been carried out by different researchers to improve the performance of the EC system. The major factors that significantly affect the performance of the EC system are air flow rate, condition of ambient air like dry bulb temperature, humidity, etc., the water flow rate through the cooling pads, thickness, density, and material of cooling pads [ 8 , 9 , 10 , 11 , 12 , 13 ]. The selection of the wet media pad material depends on many factors such as safety, cost, availability, effectiveness, and application [ 14 ].…”
Section: Introductionmentioning
confidence: 99%